NUMERICAL DYNAMIC ANALYSIS OF STIFFENED PLATES UNDER BLAST LOADING - TAVAKOLI, HAMIDREZA (2013)
USING THE GENERAL PURPOSE FINITE ELEMENT PACKAGE ABAQUS, AN INVESTIGATION HAS BEEN CARRIED OUT TO EXAMINE THE DYNAMIC RESPONSE OF STEEL STIFFENED PLATES SUBJECTED TO UNIFORM BLAST LOADING. THE MAIN OBJECTIVE OF THIS STUDY IS TO DETERMINE THE DYNAMIC RESPONSE OF THE STIFFENED PLATES CONSIDERING THE EFFECT OF STIFFENER CONFIGURATIONS. SEVERAL PARAMETERS, SUCH AS BOUNDARY CONDITIONS, MESH DEPENDENCY AND STRAIN RATE, HAVE BEEN CONSIDERED IN THIS STUDY. SPECIAL EMPHASIS IS FOCUSED ON THE EVALUATION OF MIDPOINT DISPLACEMENTS AND ENERGY OF MODELS. THE MODELING TECHNIQUES WERE DESCRIBED IN DETAILS. THE NUMERICAL RESULTS PROVIDE BETTER INSIGHT INTO THE EFFECT OF STIFFENER CONFIGURATIONS ON THE NONLINEAR DYNAMIC RESPONSE OF THE STIFFENED PLATES SUBJECTED TO UNIFORM BLAST LOADING.